Converging projections from the mediodorsal thalamic nucleus and mesencephalic dopaminergic neurons to the neocortex in three species. - Divac, I; Björklund, A; Lindvall, O; Passingham, R (1978)
Previous studies in the rat have shown that the neocortical dopaminergic afferents, originating in the mesencephalon, terminate in those areas of the frontal lobe which receive projections from the mediodorsal thalamic nucleus i.e., the prefrontal cortex. In order to clarify whether this overlap is accidental for the rat or a consistent feature of several species we have compared the projection areas of the ventral tegmental area and the mediodorsal thalamic nucleus in three species, rat, opossum and tree shrew, using HRP injections in combination with glyoxylic acid histofluorescence method. The results have shown, first, that the area innervated by the mediodorsal nucleus of the thalamus is localized in a different part of the frontal lobe in each species: dorsolateral in the opossum, anteromedial, polar and suprarhinal in the rat and frontopolar in the tree shrew. Secondly, this area alone in each species receives projections from the ventral tegmental area. Thirdly, this area alone receives a dense innervation in the deep cortical layers by fluorescent fibres probably containing dopamine. The neighbouring neocortical areas receive afferents neither from the mediodorsal nucleus of the thalamus nor from the ventral mesencephalic tegmentum; their catecholamine innervation is mainly confined to the superficial layers and appears to be of noradrenergic nature. Although the techniques used did not allow a precise determination of the borders of the two projection areas and, therefore, the exact degree of overlap, it appears that mesencephalic dopaminergic innervation is a characteristic feature of the prefrontal cortex in the mammalian brain.